Post-COVID Sustainable Economic Development - Andrijasevic, Maja; Tomic, Vesna Pasic; Jovanovic, Violeta (Problemy Ekorozwoju, 2021)
Crises show all the vulnerability and unsustainability of modern economic systems, imposing the need to ask ourselves what really is important, what wealth actually is. At the same time, they are an opportunity to critically review economic systems, ideologies, economic indicators of quality of life and dogmatically set ideas which have negative impacts on society, culture and the environment. In this sense, the current pandemic is an opportunity to take action and make a change, to shift the focus to socio-economic models focused on people, environment and strengthening of global partnership for sustainable development.